Italy : 2006 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Italy. (IMF Staff Country Reports; Country Report ;, 2007)
This 2006 Article IV Consultation highlights that Italy's economy is enjoying a broad-based, if comparatively modest, cyclical upswing. Output is estimated to have grown by 1 3/4 percent in 2006-the strongest pace since the beginning of the decade. Inflation is close to that of the euro area, financial conditions are favorable, unemployment is falling, and the current account deficit is moderate. Some progress has been made on broad-based structural reform. Recent initiatives in labor contracting envision a partial rollback of earlier liberalizing reforms.